2009
DOI: 10.1002/pssa.200824332
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and optical properties of Eu2+ doped CaGa2S4–CaS composite bicolor phosphor for white LED

Abstract: In the present paper, we report the optical properties of the bicolor composite phosphor on the base of CaS and Ga2S3 and study the possibility using this composite to obtain a white light LED. In particular, the energy transfer between the green and red emission bands of the bicolor composite phosphor activated by Eu2+ ions was studied. (© 2009 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…As the quantum efficiency of CaGa 2 S 4 :Eu and Sr 2 Ga 2 S 5 :Eu was reported to be similar to that of YAG:Ce [174], the thiogallates recently attracted attention as color conversion phosphor as well [174,175,176,177,178,179]. The emission band width is considerably smaller than in YAG:Ce, which necessitates the use of at least a second, red-emitting phosphor to produce white light starting from a blue LED.…”
Section: Color Conversion Phosphorsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the quantum efficiency of CaGa 2 S 4 :Eu and Sr 2 Ga 2 S 5 :Eu was reported to be similar to that of YAG:Ce [174], the thiogallates recently attracted attention as color conversion phosphor as well [174,175,176,177,178,179]. The emission band width is considerably smaller than in YAG:Ce, which necessitates the use of at least a second, red-emitting phosphor to produce white light starting from a blue LED.…”
Section: Color Conversion Phosphorsmentioning
confidence: 99%
“…The emission band width is considerably smaller than in YAG:Ce, which necessitates the use of at least a second, red-emitting phosphor to produce white light starting from a blue LED. Several authors reported the combination of CaS:Eu and CaGa 2 S 4 :Eu [175,177,179], even with a ‘one pot synthesis’ based on the observation that a CaS:Ga 2 S 3 starting ratio higher than 1:1 leads to a mixture of CaS:Eu and CaGa 2 S 4 :Eu. Taking into account that CaS:Eu has a much more severe concentration quenching behavior compared to CaGa 2 S 4 :Eu, it is questionable whether this synthesis approach is optimal in terms of overall quantum efficiency of the mixture.…”
Section: Color Conversion Phosphorsmentioning
confidence: 99%
“…[6][7][8][9][10] Currently, a rare-earth activator is the most promising approach for energy efficient red phos-phors for fluorescent lamps and WLEDs. The most successful materials are rare-earth-doped sulfates and (oxy)nitrides, [11][12][13][14][15][16][17][18] such as Eu 2+ -doped CaS, Eu 3+ -doped Y 2 O 2 S and Eu 2+ -doped CaAlSiN 3 . Nevertheless, the poor chemical stability and critical syntheses conditions of these air-and moisture-sensitive sulfides/nitrides make them unfavorable as competitive candidates for advanced WLEDs.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the nitride red phosphors, such as MAlSiN 3 :Eu 2+ and M 2 Si 5 N 8 :Eu 2+ (M = Ca, Sr, Ba), that have been popularly applied in WLEDs are very costly, despite of their excellent performance in luminescent efficiency and thermal stability . Nevertheless, the sulfate red phosphors, such as CaS:Eu 2+ , Sr(S,Se):Eu 2+ , (Sr,Ca)Ga 2 S 4 :Eu 2+ , or (Y,La) 2 O 2 S:Eu 3+ , are chemically unstable when exposed to a humid environment . Furthermore, the Ni/Ag electrodes of an LED chip tend to react with sulfur to form black compounds, which prominently affect the extraction of emitted photons.…”
Section: Introductionmentioning
confidence: 99%